Keeping confidentiality of sensitive attributes in credential during trust negotiation - LIAO Jun-guo1; HONG Fan2; LI Jun2; YANG Mu-xiang2 (Tongxin xuebao)
The scheme,called SDSA（selectively disclosing sensitive attributes）,was proposed to keep confidentiality of sensitive attributes in credential,which had the following characteristics,such as selectively disclosing sensitive attributes in credential,simple key management,no need of the secure third party.The security of SDSA is proved.The application and implementation of SDSA is illuminated through a typical example.